Diversity and functional structure of soil animal communities suggest soil animal food webs to be buffered against changes in forest land use - Melanie M. Pollierer; Bernhard Klarner; David Ott; Christoph Digel; Roswitha B. Ehnes; Bernhard Eitzinger; Georgia Erdmann; Ulrich Brose; Mark Maraun; Stefan Scheu (Oecologia, 2021)
Forest soil and litter is inhabited by a diverse community of animals, which directly and indirectly rely on dead organic matter as habitat and food resource. However, community composition may be driven by biotic or abiotic forces, and these vary with changes in habitat structure and resource supply associated with forest land use. To evaluate these changes, we compiled comprehensive data on the species composition of soil animal communities and environmental factors in forest types varying in land-use intensity in each of three regions in Germany, i.e., coniferous, young managed, old managed, and unmanaged beech forests. Coniferous forests featured high amounts of leaf litter and low microbial biomass concentrations contrasting in particular unmanaged beech forests. However, soil animal diversity and functional community composition differed little between forest types, indicating resilience against disturbance and forest land use. Structural equation modelling suggested that despite a significant influence of forest management on resource abundance and quality, the biomass of most soil fauna functional groups was not directly affected by forest management or resource abundance/quality, potentially because microorganisms hamper the propagation of nutrients to higher trophic levels. Instead, detritivore biomass depended heavily on soil pH. Macrofauna decomposers thrived at high pH, whereas mesofauna decomposers benefitted from low soil pH, but also from low biomass of macrofauna decomposers, potentially due to habitat modification by macrofauna decomposers. The strong influence of soil pH shows that decomposer communities are structured predominantly by regional abiotic factors exceeding the role of local biotic factors such as forest type.

Soil moisture trends in the Czech Republic between 1961 and 2012 - M. Trnka; R. Brázdil; M. Možný; P. Štěpánek; P. Dobrovolný; P. Zahradníček; J. Balek; D. Semerádová; M. Dubrovský; P. Hlavinka; J. Eitzinger; B. Wardlow; et al. (International Journal of Climatology, 2015)
Central Europe is generally not considered a drought‐prone region compared with, for example, the Mediterranean. However, Central Europe, including the Czech Republic, recently experienced a series of drought events with substantial impacts, especially on crop production. Because agriculture systems, and vegetation in general, have adapted to evenly distributed precipitation, the region is susceptible to even short‐term droughts. The recent drought events may be the result of multi‐decadal climate variability or a more general trend, with some studies showing a link to a more frequent occurrence of atmospheric circulation patterns that are conducive to drought. This study introduces an innovation to the standard methodological approaches in evaluating drought climatology by analysing soil moisture conditions over more than 50 years. This approach relies on state‐of‐the‐art observed weather data and state‐of‐the‐art soil moisture model data, and focuses on the dynamic simulation of soil moisture content with high temporal (daily) and spatial (500 m) resolution in a diverse landscape. Statistically significant trends of decreasing soil moisture content were found, notably during May and June between 1961 and 2012. In contrast, trends towards higher soil moisture content were noted during the October–March time period. When the periods of 2001–2012 and 1961–1980 were compared, the probability of drought between April and June was found to increase by 50%. This indicates a loading of the ‘climate dice’ towards drier conditions. The probability of extreme drought events has also been found to increase. These results support concerns about the potentially increased severity of drought events in Central Europe under projected climate change.

Effects of prey quality and predator body size on prey DNA detection success in a centipede predator - B. Eitzinger; E. M. Unger; M. Traugott; S. Scheu (Molecular Ecology, 2014)
Predator body size and prey quality are important factors driving prey choice and consumption rates. Both factors might affect prey detection success in PCR ‐based gut content analysis, potentially resulting in over‐ or underestimation of feeding rates. Experimental evidence, however, is scarce. We examined how body size and prey quality affect prey DNA detection success in centipede predators. Due to metabolic rates increasing with body size, we hypothesized that prey DNA detection intervals will be shorter in large predators than in smaller ones. Moreover, we hypothesized that prey detection intervals of high‐quality prey, defined by low carbon‐to‐nitrogen ratio will be shorter than in low‐quality prey due to faster assimilation. Small, medium and large individuals of centipedes L ithobius spp. ( L ithobiidae, C hilopoda) were fed C ollembola and allowed to digest prey for up to 168 h post‐feeding. To test our second hypothesis, medium‐sized lithobiids were fed with either D iptera or L umbricidae. No significant differences in 50% prey DNA detection success time intervals for a 272‐bp prey DNA fragment were found between the predator size groups, indicating that body size does not affect prey DNA detection success. Post‐feeding detection intervals were significantly shorter in Lumbricidae and Diptera compared to Collembola prey, apparently supporting the second hypothesis. However, sensitivity of diagnostic PCR differed between prey types, and quantitative PCR revealed that concentration of targeted DNA varied significantly between prey types. This suggests that both DNA concentration and assay sensitivity need to be considered when assessing prey quality effects on prey DNA detection success.

Lack of energetic equivalence in forest soil invertebrates - Roswitha B. Ehnes; Melanie M. Pollierer; Georgia Erdmann; Bernhard Klarner; Bernhard Eitzinger; Christoph Digel; David Ott; Mark Maraun; Stefan Scheu; Ulrich Brose (Ecology, 2014)
Ecological communities consist of small abundant and large non‐abundant species. The energetic equivalence rule is an often‐observed pattern that could be explained by equal energy usage among abundant small organisms and non‐abundant large organisms. To generate this pattern, metabolism (as an indicator of individual energy use) and abundance have to scale inversely with body mass, and cancel each other out. In contrast, the pattern referred to as biomass equivalence states that the biomass of all species in an area should be constant across the body‐mass range. In this study, we investigated forest soil communities with respect to metabolism, abundance, population energy use, and biomass. We focused on four land‐use types in three different landscape blocks (Biodiversity Exploratories). The soil samples contained 870 species across 12 phylogenetic groups. Our results indicated positive sublinear metabolic scaling and negative sublinear abundance scaling with species body mass. The relationships varied mainly due to differences among phylogenetic groups or feeding types, and only marginally due to land‐use type. However, these scaling relationships were not exactly inverse to each other, resulting in increasing population energy use and biomass with increasing body mass for most combinations of phylogenetic group or feeding type with land‐use type. Thus, our results are mostly inconsistent with the classic perception of energetic equivalence, and reject the biomass equivalence hypothesis while documenting a specific and nonrandom pattern of how abundance, energy use, and biomass are distributed across size classes. However, these patterns are consistent with two alternative predictions: the resource‐thinning hypothesis, which states that abundance decreases with trophic level, and the allometric degree hypothesis, which states that population energy use should increase with population average body mass, due to correlations with the number of links of consumers and resources. Overall, our results suggest that a synthesis of food web structures with metabolic theory may be most promising for predicting natural patterns of abundance, biomass, and energy use.